2017
DOI: 10.1177/1479164116680776
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications of myocardial perfusion imaging and coronary calcium score in a Macedonian cohort of asymptomatic patients with type 2 diabetes

Abstract: Aim: Type-2 diabetes is a risk factor for coronary artery disease (CAD), however, a number of studies have shown that patients are asymptomatic for CAD. The presence of CAD in asymptomatic patients with type-2 diabetes were evaluated to determine its impact on management decision and prognosis.Methods: Seventy five patients underwent SPECT myocardial perfusion imaging for detection of suspected CAD. We used 17 segment model for perfusion and function analysis. Multislice computed tomography was performed in 45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The complicated lesions, such as diffuse and calcified lesion, are often presented in the coronary stenosis related with DM [3] . The relationship between complicated nonobstructive and atherosclerotic calcification lesions with DM-related silent myocardial ischemia has been reported, but its mechanism remains unsolved [4] , [5] . The diagnostic delay often causes fatal cardiovascular events, and then it is desired to develop the specific screening tool for silent myocardial ischemia.…”
Section: Introductionmentioning
confidence: 99%
“…The complicated lesions, such as diffuse and calcified lesion, are often presented in the coronary stenosis related with DM [3] . The relationship between complicated nonobstructive and atherosclerotic calcification lesions with DM-related silent myocardial ischemia has been reported, but its mechanism remains unsolved [4] , [5] . The diagnostic delay often causes fatal cardiovascular events, and then it is desired to develop the specific screening tool for silent myocardial ischemia.…”
Section: Introductionmentioning
confidence: 99%
“…[25] Prognostic value of MPI and CCS was also established in our previous studies. [2627] There is an ongoing debate whether ischemia-based management in both symptomatic and asymptomatic patients with suspected or established stable CAD could change prognosis. Several studies such as COURAGE and BARI 2D have not shown any prognostic advantages of invasive management of patients with stable CAD.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, CAD as a major cause of morbidity, mortality, and financial costs in patients with T2DM, could be asymptomatic in 20-35% of diabetic patients (3). However, acute myocardial infarction (MI) and sudden cardiac death might be often the initial presentations (4,5). Developing at a younger age, higher rate of multi-vessel disease and being more prone to have complications after MI, such as congestive heart failure, are some of the features indicating the overall poorer outcome of CAD in diabetic patients (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that myocardial perfusion imaging (MPI) is a reliable technique for risk assessment of CAD in diabetic patients (10)(11)(12). It is still under debate whether screening myocardial ischemia is rational in asymptomatic diabetic patients compared to standard therapeutic strategies and whether it improves the risk stratification, management, and prognosis in different patient groups (4). Therefore, the aim of this study was to assess CAD risk, prevalence and Predicting Factors of an Abnormal Gated Myocardial Perfusion SPECT in Asymptomatic Patients with Type 2 Diabetes .…”
Section: Introductionmentioning
confidence: 99%